The state regulation of the economic activities in domestic pharmacy: regulatory aspect: uk. - Zlahoda, V. S.; Ivko, T. I.; Germanyuk, Т. А.; Bobrytska, L. O. (Social Pharmacy in Health Care, 2021)
In modern working conditions, a pharmacist has insufficient knowledge of regulatory documents regulating the activities of the pharmaceutical industry. Thus, there is a need to provide informational assistance to the pharmacist by systematizing the current legal documents. Aim. To scientifically generalize legal acts on the state regulation of the business entity in pharmacy in Ukraine. Materials and methods. Regulatory legal acts regulating the process of the state regulation of the activity of an economic entity in pharmacy in Ukraine, and such methods as content analysis, generalization were used. Results. As a result of the content-analysis it has been found that state supervision (control) of the pharmaceutical market of Ukraine is performed by the following state structures: the State Service of Ukraine for Medicines (Drugs) and Drug Control, the State Service of Ukraine for Food Safety and Consumer Protection, the State Fiscal Service, the State Labor Service of Ukraine, the State Emergencies Service of Ukraine. Conclusions. When conducting the content-analysis it has been found that the legal documents regulating the process of pharmaceutical care provision in Ukraine are the Laws of Ukraine “On licensing of the economic activities”, “On consumer protection”, “On labor protection”. A graphic model of the state regulation of the business entity’s activity in Ukraine has been also created. Key words: state regulation; business entity in pharmacy; regulatory legal acts; content-analysis.